1993
DOI: 10.1091/mbc.4.10.1017
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of yeast geranylgeranyl transferase I defect by alternative prenylation of two target GTPases, Rho1p and Cdc42p.

Abstract: Geranylgeranyl transferase I (GGTase I), which modifies proteins containing the sequence Cys-Ali-Ali-Leu (Ali: aliphatic) at their C-termini, is indispensable for growth in the budding yeast Saccharomyces cerevisiae. We report here that GGTase I is no longer essential when Rho1p and Cdc42p are simultaneously overproduced. The lethality of a GGTase I deletion is most efficiently suppressed by provision of both Rho1p and Cdc42p with altered C-terminal sequences (Cys-Ali-Ali-Met) corresponding to the C-termini of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 50 publications
2
58
0
Order By: Relevance
“…This result confirmed that Chs4p is prenylated in vivo. Since prenylation is an irreversible process, we assume that if Chs4p is preferentially farnesylated, inactivation of endogenous FTase will increase the amount of unmodified Chs4p available as a substrate for reaction in vitro, even if crossspecificity between FTase and GGTase I are observed (29,31,41). To prove the involvement of FTase in modification of Chs4p, we immobilized TAP-Chs4p expressed in wt yeast cells or cells lacking the catalytic subunit of FTase (Ram1p) on IgG-Sepharose beads and used the resin-Chs4p as a substrate for FTase assays in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result confirmed that Chs4p is prenylated in vivo. Since prenylation is an irreversible process, we assume that if Chs4p is preferentially farnesylated, inactivation of endogenous FTase will increase the amount of unmodified Chs4p available as a substrate for reaction in vitro, even if crossspecificity between FTase and GGTase I are observed (29,31,41). To prove the involvement of FTase in modification of Chs4p, we immobilized TAP-Chs4p expressed in wt yeast cells or cells lacking the catalytic subunit of FTase (Ram1p) on IgG-Sepharose beads and used the resin-Chs4p as a substrate for FTase assays in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…3 show that chs4-C693S yeast cells harboring the nonprenylated version of Chs4p are more resistant to CFW than are wt cells and less resistant than are chs4⌬ yeast cells. To confirm the role of prenylation of Chs4p, we also constructed a chs4-I695L,M696L yeast strain expressing Chs4p with the C-terminal CVLL motif (the CVLL motif present in yeast Rho1p was proven experimentally to be a substrate for geranylgeranyl transferase type I [31]). Geranylgeranylation of Chs4p only partially restores the sensitivity to CFW.…”
Section: Vol 6 2007 Chitin Synthesis In S Cerevisiae 331mentioning
confidence: 99%
“…Correct cellular targeting is essential for the function of Rho GTPases (Ohya et al, 1993). One aspect of Rho GTPase function is to localize effectors and other proteins required for polarization to the imminent growth site (Johnson, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…These include the proposed GTP-binding and hydrolysis domains (GDGAVGKT and DTAGQE), a GDP to GTP exchange domain (TKLD), a domain for effector interaction (TVFDNY), and a C terminal CAAX motif (where A indicates an aliphatic amino acid and X any amino acid), which is predicted to allow association with the plasma membrane after prenylation (Ohya et al, 1993;Ziman et al, 1991;Chen et al, 1993).…”
Section: Magnoportha Grisea (Af267176) and Suillus Bovinus (Af235004)mentioning
confidence: 99%
“…Although GGTase I normally is an essential gene for growth, it can be made non-essential, whenthe dosage of the two GTPases, Rholp (30) and Cdc42p (22), are artificially elevated (41). Since the yeast GGTase I prenylates these two GTPases, Cdc42p and Rholp are implicated genetically as the two essential substrates of GGTase I (41).…”
mentioning
confidence: 99%